Gerontological Variations on the Language Use and Attitudes of Southern Philippine Plurilingual Communities - Jeconiah Louis Dreisbach, (Development in Language Studies, 2024)
This pioneering research explores the correlation of gerontological factors in sociolinguistics in the intergenerational language attitudes of Southern Philippine plurilingual communities on the Cebuano, Filipino, and English languages. Specifically, viewpoints of Cebuano speakers from the cities of Cebu and Davao in southern Philippines were investigated in this study. Utilizing mixed methods research, results found that the elder generation may prefer their children to learn the Cebuano language but this does not result in fruition as their beliefs in the English language prevent this from happening. Generation Z emphasized that the English and Filipino languages affected their fluency in the Cebuano language. They ended up speaking English for formal communication as the elder generation accentuated its role as an international language. While a majority of the respondents from both generations preferred the use of the Cebuano language for everyday communication, the actual count of their results deviated from the expected count that coincides with the null hypothesis. Consequently, this study confirms that gerontological variations affect the respondents’ language attitudes on everyday communication. Lastly, no significant differences were in their views that English should be used for formal communication and the maintenance of Filipino as the Philippine national language